Fluctuating temperatures extend median lifespan, improve reproduction and reduce growth in turquoise killifish - Žák, Jakub; Reichard, Martin (Experimental gerontology, 2020)
In natural populations, individuals experience daily fluctuations in environmental conditions that synchronise endogenous biorhythms. Artificial alterations of environmental fluctuations can have negative consequences for life history traits, including lifespan. In laboratory studies of aging, the role of fluctuating temperature is usually overlooked and we know little of how thermal fluctuation modulates senescence in vertebrates. In this longitudinal study we followed individually-housed turquoise killifish, Nothobranchius furzeri, from two thermal regimes; ecologically relevant diel fluctuations (20 °C - 35 °C) and stable temperature (27.5 °C), and compared their survival, growth and reproduction. Fish experiencing fluctuating temperatures had a longer median lifespan but reached smaller asymptotic body size. Within-treatment variation indicated that extended lifespan in fluctuating temperatures was not causally linked to decreased growth rate or smaller body size, but occurred solely due to the effect of thermal fluctuations. Male body size was positively associated with lifespan in stable temperatures but this relationship was disrupted in fluctuating thermal regimes. Females exposed to fluctuating temperatures effectively compensated egg production for their smaller size. Thus, there was no difference in absolute fecundity between thermal regimes and body-size corrected fecundity was higher in females in fluctuating temperatures. Overall, despite a brief exposure to sub-optimal thermal conditions during fluctuations, fluctuating temperature had a positive effect on survival and reproduction. These results suggest that the expression of life history traits and their associations under stable temperatures are a poor representation of the relationships obtained from ecologically relevant thermal fluctuations.
Keywords: dlouhověkost; longitudinální studie; Humans; rozmnožování; Fundulidae; zvířata; ženské pohlaví; teplota; Temperature; Female; mužské pohlaví; Longevity; Male; Animals; Reproduction; lidé; Longitudinal Studies